STUDY ON THE ROLE OF WOMEN WORKERS IN THE AGRICULTURE SECTOR OF BIHAR - MD.ENAYATULLAH (International Journal of Multidisciplinary Research and Studies, 2020)
Agriculture was the very first kind of culture that man learnt to practise as a method to provide for himself, and it was the first sort of culture that man learned to practise. It is the most important part of every economy, regardless of how long it has been operating or how developed it now is. In India, agriculture is often carried on as a family enterprise. At the same time, it is an essential driver of rural development and the reduction of rural poverty. It is regarded as the economic pillar that supports rural communities in India. Agriculture is the single most major source of employment in India, especially for rural women, and as a result, agriculture plays an incredibly important role in ensuring that India's economy will continue to be stable. Only around 17–18 percent of India's Gross Domestic Product (GDP) comes from the country's agricultural sector. Statistics from 2012 indicate that India's agriculture sector is now the fourth largest in the world.